A Global Research Productivity of Green Marketing: A Scientometric Study - Ravi, S; Palaniappan, M. (Journal of Data Science, Informetrics, and Citation Studies)
The term “Green marketing” has been used as a search keyword in the global indexing database ‘Web of Science’ a core collection which is initially published by the Institute for Scientific Information founded by the international information scientist Eugene Garfield. It is found from the study that there are 7178 scholarly publications. The different scientometric indicators, year wise, document types, Author productivity, highly cited journals, highly productive institutions, three fields’ plots, highly cited countries, and Country collaboration map. The highest number of publications was produced in the year 2019 with 997 documents; the value of h-index was high in the year 2013 with 86 counts and articles are the highest with 6300 the highest h-index was found by the author Wang J and The highest value of h-index 86 were produced by journal of cleaner Production and 135 g-index and highly productive institutions were Hong Kong Polytechnic University with 65 (1%) publications and received 5798 citations and the top three writers, namely Dangelico RM, Sarkis JS, and Chen YS. The top three subject areas, sustainability, green marketing, and sustainable development, and the top 20 cited references lead to 3095 citations authored by Fornell C (1981) secured the highest citations (307) and the highest article contributed with the USA 1416 and the highest h-index with Canada 36, From China to the USA collaboration with 142 times.
Keywords: Green Marketing; Three field plots; Scientometric; Research publication; Environmental marketing; Ecological marketing.